Oleum Baeticum: Economía y política em el Imperio Romano - Funari, Pedro Paulo Abreu (Revista de Estudos Filosóficos e Históricos da Antiguidade, 2025)
The Spanish Royal History Academy (Real Academia de la Historia) founded in 1738 gathers 36 leading historians in a variety of specialties and is one the most prestigious scholarly institutions in the historical sciences, including archaeology. Among its activities, such as the interaction with similar institutions in other countries and the participation in the Union Académique Internationale, scholarly publications are an outstanding and most enduring endeavor.